The role of human papillomavirus in oral squamous cell carcinoma: myth and reality - Kansy, Julia Katharina; Thiele, Oliver C.; Freier, Kolja (Oral and maxillofacial surgery, 2014)
IntroductionAs the traditional risk factors for oral squamous cell carcinoma, especially tobacco, decline, new potential causative agents become the focus of research. Since the discovery of human papillomavirus (HPV) and its importance in carcinogenesis in cervical cancer, a lot of research has been undertaken to define its role in different types of cancer. In the present study, we evaluate the role of high-risk HPV types in initiation and progression of oral squamous cell carcinoma (OSCC) using a systematic review of the current literature.Material and methodsA literature research with the search term “HPV oral squamous cell carcinoma” was performed via PubMed. Results were screened systematically for relevance and classified into the following categories: molecular biology, genetics, clinical aspects, and prevalence. Articles were then further analyzed to assess quality.ResultsThe literature research led to 527 results, with an overall HPV prevalence of 30.1 % in OSCCs. The most frequently identified subtypes were HPV-16 and HPV-18 (25.4 and 18.1 %, respectively). Prognostic relevance of HPV was discussed controversially. HPV detection via polymerase chain reaction is the most established method today. Molecular changes according to carcinogenic pathways described for cervix carcinoma were not routinely found in OSCC. In general, no definite role of high-risk HPV is currently deducible from the literature.ConclusionsHigh-risk subtypes 16 and 18 are present in the genome in approximately one third of OSCC. Its role as a causative agent is less clear than the role in oropharyngeal tumors. The infection might not be the cause of carcinogenesis in a significant number of patients but may become proportionally more important with the decrease of the classical risk factors of tobacco and alcohol.
Published online: 16 December 2012
First online: 16 December 2012
Gesehen am 21.06.2018